TEACHING COMMUNICATIVE TRANSLATION: AN ACTIVE RECEPTION ANALYSIS BETWEEN THE TRANSLATION AND READER'S RECEPTION - Venny Eka Meidasari (English Review: Journal of English Education, 2014)
Abstract:Â Literary theory sees reception theory from the reader response that emphasizes the reader's reception of a literary text. It is generally called audience reception in the analysis of communications models. In literary studies, reception theory originated from the work of Hans-Robert Jauss in the late 1960s. Communication only means that the original message will be clearly sent in its equivalent context to the target receptor. Similarly, the main role of translators is to send the message across without any form of distortion or emphasis. It is delivering the genuine context of the message to the language that the active receptor understands. A single mistake in a context translation can result to offensive message that can eventually lead to misunderstandings between active receptors. This paper proposes on the role of translator as the mediator between a writer of the original text and the active target language receptors of translated version in the course of communication which definitely affects the process and result of translation practice. It also reveals the emphasis on the creation text of the translation theories originated from the strategic communication theories, which hopefully leads to a dream of the most equivalence between the text and the translated version.Keywords: translator, active receptor, mediator, strategic communication, equivalence.Â